On the Evaluation of Common-Sense Reasoning in Natural Language Understanding - Cheung, Jackie Chi Kit; Trichelair, Paul; Emami, Ali; Cheung, Jackie Chi Kit; Trischler, Adam; Suleman, Kaheer; Diaz, Fernando (Critiquing and Correcting Trends in Machine Learning NeurIPS 2018 Workshop, 2018)
The NLP and ML communities have long been interested in developing models capable of common-sense reasoning, and recent works have significantly improved the state of the art on benchmarks like the Winograd Schema Challenge (WSC). Despite these advances, the complexity of tasks designed to test common-sense reasoning remains under-analyzed. In this paper, we make a case study of the Winograd Schema Challenge and, based on two new measures of instance-level complexity, design a protocol that both clarifies and qualifies the results of previous work. Our protocol accounts for the WSC’s limited size and variable instance difficulty, properties common to other common-sense benchmarks. Accounting for these properties when assessing model results may prevent unjustified conclusions.